Prevalence of and factors associated with likely obstructive sleep apnea in individuals with airflow limitation - Kim, Sang Hyuk; Sim, Jae Kyeom; Choi, Jee Yea; Moon, Ji-Yong; Lee, Hyun; Min, Kyung Hoon (Frontiers in Medicine, 2024)
Introduction: Obstructive sleep apnea (OSA) is frequently associated with airflow limitation (AFL). However, information on the prevalence of and factors associated with likely OSA in individuals with AFL in Korea is limited. Methods: Data from the 2019 Korea National Health and Nutrition Examination Survey (KNHANES) were used, and 3,280 individuals (2,826 individuals without AFL and 454 individuals with AFL) were included. AFL was defined as forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) < 0.7. A score ≥ 5 on the STOP-BANG questionnaire was used to identify individuals with likely OSA. The prevalence of likely OSA was compared between individuals with and without AFL. In addition, factors associated with likely OSA in individuals with AFL were evaluated using multivariable logistic regression analysis. Results: Of 3,280 individuals, 13.8% had an AFL. The prevalence of likely OSA was significantly higher in individuals with AFL than in individuals without AFL (9.2% vs. 5.0%, p = 0.014). Among 454 individuals with AFL, obesity (adjusted odds ratio (aOR) = 14.78, 95% confidence interval (CI) = 4.20–52.02) was most strongly associated with likely OSA, followed by heavy alcohol consumption (aOR = 4.93, 95% CI = 1.91–12.70), hypertension (aOR = 4.92, 95% CI = 1.57–15.46), overweight (aOR = 4.71, 95% CI = 1.76–12.64), college graduate (aOR = 4.47, 95% CI = 1.10–18.22), and history of pulmonary tuberculosis (aOR = 3.40, 95% CI = 1.06–10.96). Conclusions: In Korea, approximately 1 in 10 individuals with AFL had likely OSA. Overweight and obesity, heavy alcohol consumption, high educational level, hypertension, and history of tuberculosis were associated with likely OSA in individuals with AFL.